Jawi games: interactive learning for kids 10-12 years old by applying game-based learning principles / Nur Anis Syahirah Ahmad ... [et al.] - Ahmad, Nur Anis Syahirah; Nasrudin, Nur Hasni; Azmi, Anis Zafirah; Ahmad Junid, Rosida (2020)
Jawi has enormous significance in the history of the nation. Jawi is also one of Malay scripts that has very close relationship with Islam, Malay race and Malay heritage. Jawi is also important such the beginning to learn and read Al-Quran. But nowadays Jawi is no longer relevant because no commercial value among readers and community. The aim of this study is to propose the use of Jawi for children to learn by using interactive games. The lack of Jawi use and the notion that difficult to learn, make the young generation now beginning to forget Jawi. Jawi should be learnt during the childhood. Looking at the trend of childhood is now over to modern technology such as is more like to learn in the fun way, so from that Jawi interactive learning game should be to attract children to learn about Jawi. Nowadays, some parents prefer to use books and another learning method such as flash card as material of teaching but as we can see, the children may give some reasons or take times for the children to open and take the books to prepare during learning times compared to open PC's and playing games. The focus of this Jawi games is to develop Jawi games for children from 10 to 12 years. To evaluate the usability and the effectiveness of Jawi games that has been developed by applying game-based learning principles [1]. This project has been successfully developed by using Agile Model Methodology.